Особенности и рaзличия aдеквaтного и эквивaлентного переводa (Вестник КазНУ. Серия Востоковедения, 2018)
All through history success or failure of intercultural communication depends on the level of adequacyand equivalency of source text with its translation in target language. So, many scientists focusedon studying terms of adequacy and equivalency. As a result, it increased the number of theories orientedon studying this subject matter. Some of the researchers say that adequacy and equivalency are samethings; others think that these terms differ but have many similarities. So, absence of explicit definitionsfor the terms adequacy and equivalency, increases the need for distinguish them from each other.Therefore, purpose of this work is distinguishing adequacy from equivalency by systematization andclassification of theories about adequate and equivalent translation. In one hand it will help to reader toeasily understand what is adequacy or equivalency in translation studies, from the second hand we candetermine their similarities and differences. In order to achieve purpose of research, we use the methods of comparative analysis in the process of implementing of our work.Based on the research of foreign scientists, we analyzed similarities and differences of adequate and equivalent translation. According to this analysis, we think that an adequate translation provides the expected communicative effect, and one of its main requirements is the use of equivalents to ensure maximum transmission of meaning of the original. But, equivalent translation cannot always provide pragmatic tasks and meet the conventional normative requirements for translation.